Gender Equality Narratives in the Digital Space: An Analysis of Banten Women's Political Representation through Podcasts - Nurjuman, Husnan; Dewantie, Jessie; Fitriana, Rina (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital space has opened up new opportunities for female politicians to negotiate their identities and expand their representation beyond the boundaries of conventional media. This study aims to analyze how female members of the Banten Regional People's Representative Council (DPRD) construct gender equality narratives through podcasts on the Banten Podcast channel. Using qualitative content analysis with a social construction approach, this study examines narrative patterns, self-representation strategies, and the framing of gender issues that emerge in podcast conversations. The results reveal three main findings: first, female politicians articulate gender equality issues by combining personal experiences with structural issues, resulting in more authentic and contextual narratives; second, podcasts are used to assert political competence through discussions of the legislative process, policy evaluation, and women's substantive roles in parliament; and third, personal narratives are used as a moral legitimacy strategy that strengthens emotional closeness with the public and challenges gender stereotypes. These findings emphasize the function of podcasts as a digital democratic arena capable of expanding the space for women's political articulation and offering a more equal model of gender representation at the local level.